2020
DOI: 10.1089/ten.tea.2019.0095
|View full text |Cite
|
Sign up to set email alerts
|

External Volume Expansion Adjusted Adipose Stem Cell by Shifting the Ratio of Fibronectin to Laminin

Abstract: External volume expansion (EVE) is an effective method of adipose tissue regeneration. However, it remains unclear how EVE induces adipose tissue regeneration. In this study, we developed EVE devices to generate expanded prefabricated adipose tissue (EPAT) in rats and investigated cell proliferation, adipogenesis, and the expression of extracellular matrix (ECM) proteins during the 12 weeks suction. In addition, EPAT-generated decellularized adipose tissue (DAT) was used to assess the role of ECM proteins in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…81 EVE suction for 12 weeks gradually increased the expression of laminin and of the adipogenic genes, PPARg and CEBPa, with peaks occurring simultaneously. 54 Moreover, the adipogenicity of ADSCs reseeded onto 12-week EPAT-DAT in vitro was greater than the adipogenicity of ADSCs reseeded onto 1-week EPAT-DAT and 1-week control-DAT. These results suggested a strong relationship between laminin and adipogenic expression (Fig.…”
Section: Eve-induced Adipogenesis In Adipose Tissuesmentioning
confidence: 96%
See 1 more Smart Citation
“…81 EVE suction for 12 weeks gradually increased the expression of laminin and of the adipogenic genes, PPARg and CEBPa, with peaks occurring simultaneously. 54 Moreover, the adipogenicity of ADSCs reseeded onto 12-week EPAT-DAT in vitro was greater than the adipogenicity of ADSCs reseeded onto 1-week EPAT-DAT and 1-week control-DAT. These results suggested a strong relationship between laminin and adipogenic expression (Fig.…”
Section: Eve-induced Adipogenesis In Adipose Tissuesmentioning
confidence: 96%
“…37 In addition, the expression of fibronectin and the number of proliferating cells were increased at week 1 in EPAT, providing further evidence that EVE is involved in inducing ADSC proliferation. 54 In vitro assays showed that the proliferation rate of ADSCs in EPAT-generated decellularized adipose tissue (DAT) was higher at 1 week than at other time points. These findings confirmed that EVE-enhanced secretion of fibronectin regulates ADSC proliferation.…”
Section: Eve Induction Of Adsc Proliferation In Adipose Tissuesmentioning
confidence: 99%
“…In animals, cells are in contact with each other not only directly through these adhesion proteins but also indirectly via the extracellular matrix, ECM, kind of an extracellular "glue," which includes proteins such as collagens, fibronectins, or laminins [89][90][91]. Various adhesion proteins such as cadherins, integrins, CAM (Cell Adhesion Molecules), selectins, etc., participate in these direct or indirect contacts between cell surfaces [92][93][94].…”
Section: Direct Interactions Between Membrane Proteinsmentioning
confidence: 99%
“…In animals, cells are in contact with each other not only directly through these adhesion proteins but also indirectly via a kind of extracellular "glue" the extracellular matrix, ECM, which includes proteins such as collagens, fibronectins or laminins [96][97][98]. In plants, many different hormones also exist, and they act at a very short distance, such as ethylene, or a more considerable distance such as auxin, gibberellins, and various phyto-oestrogens.…”
Section: Direct Interactions Between Membrane Proteinsmentioning
confidence: 99%